A study on prevalence of rotavirus infection in children below 5 years, with acute gastroenteritis - Manick Dass, S.; Pattnaik, Snigdha; Amulya, K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Diarrheal diseases are among the most frequent causes of morbidity and mortality in children worldwide, especially in India. This cross sectional study was conducted to investigate the causative agent of diarrhea among children, below five years, treated at an urban tertiary care hospital, Telangana. Methods: Stool specimens were collected from 240 children under 5 years of age visiting Apollo Medical College, General Hospital in Hyderabad, hospitals due to acute diarrhea. Rapid stool antigen immunochromatograhic testing was used to diagnose rota virus diarrhea. In this test the VP 6 antigen present on the middle layer of the virus capsule is detected. Results: During the 2 months of the study period, 60 children visited the institute seeking treatment of diarrhoea. 11 (18%) of, the children were found to be positive for rota virus infection. It was also observed that, due to advent of rotavirus vaccine, incidence of diarrhea has come down. Conclusions: In our study the prevalence of rotavirus infection in children suffering from acute gastroenteritis below five years of age is 18.3%. This study is performed using an ICT rapid card test in which group A of the rotavirus is detected, the drawback of this study is other groups of rotavirus like B and C which also cause human infections are not detected. Following the rapid ICT card test which is a diagnostic test, ELISA, confirmatory test for the detection of rotavirus should also be done.